Rancang Bangun Aplikasi Kawan Pencerita Berbasis Website Menggunakan Metode Prototype - Amanat Dirgantara; Novian Adi Prasetyo; Trihastuti Yuniati (Jurnal Terapan Teknologi Informasi, 2023)
Kawan Pencerita Publisher is a company that provides opportunities for aspiring authors to develop and publish their works. Since its establishment in 2018, Kawan Pencerita Publisher has faced marketing challenges on an annual basis. To address these challenges, the company decided to create a website. A website is a collection of web pages that includes a domain or subdomain and other essential information, making it easier for users to access important details. The objective of this study is to design and develop a Kawan Pencerita Publisher website as a marketing tool, as the current sales are limited to the Instagram social media network. For the website development, the Prototype software development method is utilized. The system testing conducted for the website follows the Blackbox Testing approach, which aims to ensure its optimal performance. The test involved all 11 employees of KP Publisher. The results of the testing indicate that the system functionality is at 100%, meaning that all required functional aspects specified in the project and system requirements are successfully implemented.